2019
DOI: 10.1021/acsami.9b16704
|View full text |Cite
|
Sign up to set email alerts
|

Self-Cleaning Nanofiltration Membranes by Coordinated Regulation of Carbon Quantum Dots and Polydopamine

Abstract: Performance declination of nanofiltration (NF) membranes caused by concentration polarization (CP) and membrane fouling has severely restricted their practical application in many fields. This work reports the construction of a novel interlayer between the substrate and the selective layer of conventional composite membranes by coordinating regulation of carbon quantum dots (CQDs) and polydopamine (PDA). Unlike traditional methods that treat CP and fouling separately, the new strategy grants the membrane with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
54
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 108 publications
(54 citation statements)
references
References 64 publications
0
54
0
Order By: Relevance
“…The thickness of the selective layer was decreased, and the desalination was improved. In addition, Shao et al reported the preparation of a TFC layer by PIP and TMC in an IP process to establish a nodule structure with a cross-sectional thickness of 80-120 nm [98]. The PES substrate was coated with a mixture of CDs, CMPI, and NaOH before the IP process.…”
Section: Coating Characteristics Of Cd/polymer Compositesmentioning
confidence: 99%
See 1 more Smart Citation
“…The thickness of the selective layer was decreased, and the desalination was improved. In addition, Shao et al reported the preparation of a TFC layer by PIP and TMC in an IP process to establish a nodule structure with a cross-sectional thickness of 80-120 nm [98]. The PES substrate was coated with a mixture of CDs, CMPI, and NaOH before the IP process.…”
Section: Coating Characteristics Of Cd/polymer Compositesmentioning
confidence: 99%
“…The coating process of a PDA-CD-TFC membrane. Reprinted with permission from[98]. Copyright (2019) American Chemical Society.…”
mentioning
confidence: 99%
“…The resultant membranes exhibited high amino acid rejection and water permeation. Shao et al [82] employed CQDs as the interlayer with the aid of dopamine (PDA) to construct a CQD-intercalated (PDA-CQDs-TFC) membrane. The uniformly distributed interlayer decreased concentration polarization and membrane fouling.…”
Section: Carbon Quantum Dots (Cqd)mentioning
confidence: 99%
“…A research group [12], reported the construction of a composite membrane which also possess self-cleaning ability. CQD membrane is reported to have high permeability and selectivity.…”
Section: The Intermediate Layer Of Cqd Increases the Water Transmission Due To Increased Hydrophilicitymentioning
confidence: 99%